Performance of a new preloaded fiducial needle to guide radiation therapy of upper gastrointestinal cancers - Phan, Vinh-An; Dalfsen, Raymond; Le, Hien; Nguyen, Nam Q. (Endoscopy, 2019)
Background Insertion of fiducials to outline the targeted lesion allows image-guided radiotherapy, and is best achieved by endoscopic ultrasound (EUS). This study is a performance comparison of the new EUS-guided preloaded fiducial needle against Visicoil fiducials.Methods Technical success, visibility score, procedural time, costs, and complications for patients who underwent EUS-guided fiducial placement in upper gastrointestinal malignancies were prospectively collected.Results 60 patients with upper gastrointestinal cancers had fiducials (14 Visicoil; 46 preloaded fiducials) inserted for image-guided radiotherapy. Technical success was 100 %, with a shorter mean (standard deviation) insertion time of 0.94 minutes (0.28 minutes) vs. 5.5 minutes (1.9 minutes; P < 0.001) and higher visibility score on fluoroscopy of 2 vs. 1.18 (P < 0.001) in the preloaded group. Neither group had major complications related to fiducial insertion. The cost of consumables per patient was lower in the preloaded group at US$480 (US$124) vs. US$643 (US$123; P < 0.001).Conclusion Fiducial insertion for image-guided radiotherapy using the new preloaded needle is associated with 100 % technical success, shorter insertion time, and higher visibility, and is more cost-effective than the Visicoil system.